2001
DOI: 10.1007/s002440010225
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Accumulation and Distribution in Slaughtered Horse Kidneys from the Argentine Central Region

Abstract: In this paper we report the results of surveys conducted in Argentina between 1997 and 1998 to know the Cd concentrations in kidney from horses of different age, sex, and origin. Cd in renal cortex and medulla was positively correlated, and higher concentrations in the cortex were found. No significant differences between values from left and right kidneys of the same animal were found. An increase in Cd levels with age of animals were observed, and no sex incidence was verified in renal Cd composition. No det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…This finding is in accordance with further data from horses (Baldini et al 2000) and cattle (Rudy 2009), however, other authors found an increase of Cd with increasing age of horses (Salmi and Hirn 1981) and humans (Anke et al 1978), but a subsequent decrease at an older age. In general, the presently measured hepatic Cd concentrations were lower than further results in horses (Salmi and Hirn 1981; Baldini et al 2000; Farmer and Farmer 2000), and also lower Cd concentrations were found in the kidneys of the horses when compared to previous data (Elinder et al 1981; Salmi and Hirn 1981; Junnila et al 1987; Baldini et al 2000; Farmer and Farmer 2000; Beldomenico et al 2001). Interestingly, the measured Cd concentrations in the livers and kidneys of the horses were markedly higher compared to cattle (Rudy 2009; Waegeneers et al 2009).…”
Section: Discussioncontrasting
confidence: 57%
“…This finding is in accordance with further data from horses (Baldini et al 2000) and cattle (Rudy 2009), however, other authors found an increase of Cd with increasing age of horses (Salmi and Hirn 1981) and humans (Anke et al 1978), but a subsequent decrease at an older age. In general, the presently measured hepatic Cd concentrations were lower than further results in horses (Salmi and Hirn 1981; Baldini et al 2000; Farmer and Farmer 2000), and also lower Cd concentrations were found in the kidneys of the horses when compared to previous data (Elinder et al 1981; Salmi and Hirn 1981; Junnila et al 1987; Baldini et al 2000; Farmer and Farmer 2000; Beldomenico et al 2001). Interestingly, the measured Cd concentrations in the livers and kidneys of the horses were markedly higher compared to cattle (Rudy 2009; Waegeneers et al 2009).…”
Section: Discussioncontrasting
confidence: 57%